DYNAMICS OF THE SEMANTIC STRUCTURE OF NAMES OF CONSTRUCTION PPECESS, ACTIONS AND DOERS IN DIALECTS OF THE PRECARPATHIAN HABITATS - Bihusjak, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the dynamic processes taking place in the name of building the semantic structure of actions and their doers are prevalent dialects in the Ukrainian Precarpathians. Analysis of the materials involved different time of sections, published in the dialect dictionaries and forwarding collected by the author. Nominative units build vocabulary studied in structural and semantic ethno-linguistic aspects.